Integrating Quality by Design Principles for Elevating Bioavailability of Candesartan Cilexetil in Fast-dissolving Tablets - Thalluri, Chandra Shekar (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The present research was aimed to increase the bioavailability of Candesartan cilexetil by integrating efficient super disintegrating agents applying the principles of quality by design. Materials and Methods: This study optimized fast dissolving tablets containing Candesartan cilexetil by integrating efficient super disintegrating agents (Isabgol husk, Potato starch, F melt C) through a direct compression method. Utilizing Design of Expert version 13.0 with a response surface methodology, formulations (CC1-CC15) were systematically developed. The influence of super disintegrates on key parameters - disintegration time (Y1), drug release at 15 min (Y2), and drug release at 30 minutes (Y3) - was extensively studied to enhance Candesartan cilexetil’s dissolution properties. Results and Discussion: Comprehensive evaluation of pre- and post-compressional factors, coupled with robust in-vitro dissolution analysis, highlighted formulation CC12’s excellence, featuring rapid disintegration and maximal drug release within specified timeframes. Utilizing the DD solver guided by regression coefficients (r2), Akaike Information Criterion (AIC), and model selection criteria (MSC), kinetics and release mechanisms were elucidated. CC12 exhibited a fickian diffusion mechanism, substantiating its robust drug release profile. Additionally, shelf-life evaluation as per ICH guidelines and a comparative analysis employing the similarity factor (f2) with Atacand were conducted. Stability studies, assessed via ANOVA, indicated insignificant differences (P > 0.05) during storage. In summary, this research optimally enhanced Candesartan cilexetil’s dissolution via proficiently formulated fast dissolving tablets. The strategic integration of super disintegrating agents, driven by Design of Expert version 13.0, yielded CC12 as an optimal candidate with rapid disintegration and superior drug release. Elucidation of release kinetics and mechanisms further fortified performance assessment. Thorough stability and similarity evaluations underscored the potential of this optimized formulation for improved therapeutic outcomes. Conclusion: Fast dissolving tablets of C and esartan cilexetil were developed by optimizing selected independent variables to improve the dissolution profile. The presence of soluble polymers like Isabgol husk, potato starch and F melt C, acting as super disintegrants, played a significant role in enhancing solubility.